EDUCATION AND INEQUALITY IN THE ERA OF GLOBALISATION: COMPARATIVE POLICY INSIGHTS FROM TEN NATIONS - Zhang, Jingchun; Lee Feng, Koo; Tze Jin, Wong; Izzatul Nabila, Sarbini (Institute for Local Self-Government Maribor, 2025)
Globalisation has transformed national economies, social structures, and labour markets, presenting new opportunities but exacerbating income inequality and resource accessibility. Education is important to this shift, both as a conduit for social mobility and a factor in economic resilience. This study examines the relationship among globalisation, educational access, and economic inequality through a comparative analysis of 10 nations: the United States, Germany, Poland, Malaysia, Thailand, India, Indonesia, Bangladesh, Brazil, and Georgia. The study integrates secondary macroeconomic data from 2022 to 2023 with qualitative policy analyses. Statistical analysis employing Pearson correlation indicates minimal correlations among Gross Domestic Product (GDP) growth, secondary school enrolment, and income inequality, implying that merely increasing access to education is insufficient for achieving equitable development. Case study findings highlight that aligning education policy with labour market demands, promoting digital inclusion, and implementing decentralised governance structures substantially improves the efficacy of educational investments. India and Poland exemplify effective methods through vocational integration and equity-centered reforms, but enduring disparities in Brazil and Malaysia underscore the shortcomings of access-oriented initiatives. This study highlights the necessity of focussing on education within an integrated framework that encompasses social protection, economic inclusion, and sustainable policy development. It provides evidence-based suggestions consistent with Sustainable Development Goals 4 (Quality Education) and 10 (Reduced Inequalities), promoting inclusive educational systems that effectively address structural disparities exacerbated by globalisation.